Answers to common questions about COVID‐19 vaccines in children with cancer. Issue 12 (16th September 2022) - Caniza, Miguela A.; Homsi, Maysam R.; Bate, Jessica; Adrizain, Riyadi; Ahmed, Tarek; Alexander, Sarah; Bhattacharyya, Arpita; Copado‐Gutierrez, Jose Luis; Gutierrez, Ivan; Lim, Yan Yin; Morrissey, Lisa; Naidu, Gita; et al.
Abstract: Background: The SARS‐CoV‐2 outbreak in 2020 evolved into a global pandemic, and COVID‐19 vaccines became rapidly available, including for pediatric patients. However, questions emerged that challenged vaccine acceptance and use. We aimed to answer these questions and give recommendations applicable for use in pediatric patients with cancer by healthcare professionals and the public. Methods: A 12‐member global COVID‐19 Vaccine in Pediatric Oncology Working Group made up of physicians and nurses from all world regions met weekly from March to July 2021. We used a modified Delphi method to select the top questions. The Working Group, in four‐member subgroups, answered assigned questions by providing brief recommendations, followed by a discussion of the rationale for each answer. All Working Group members voted on each recommendation using a scale of 1 to 10, 10 being complete agreement. A "pass" recommendation corresponded to an agreement ≥7.5. Results: We selected 15 questions from 173 suggested questions. Based on existing published information, we generated answers for each question as recommendations. The overall average agreement for the 24 recommendations was 9.5 (95% CI 9.4–9.6). Conclusion: Top COVID‐19 vaccine‐related questions could be answered using available information. Reports on COVID‐19 vaccination and related topics have been published at record speed, aided by available technology and the priority imposed by the pandemic; however, all efforts were made to incorporate emerging information throughout our project. Recommendations will be periodically updated on a dedicated website.